Tactile Cartography: Means of Inclusion/Cartografia tátil: Meio de inclusão - Wanderson Levi Gonçalves dos Santos; Moises Calu de Oliveira (Universidade Estadual de Alagoas, 2020)
Tactile cartography is a branch of cartography aimed at producing maps, models, topographic charts and other materials for people with visual impairments (blind and low vision). In this sense, this work aims to contribute to discussions about the use of tactile cartography in the classroom, contribute to the expansion of the public application of this method, and in line with expanding the area of dissemination of this method. The qualitative research was conducted through literature review. Thus, it was possible to observe how the tactile object can be crucial for students' learning, both without and with disabilities, whether visual or not